Spawning site selection of brown trout in habitat restored streams - Svensson, Jonas (2012)
During the timber floating era, most of Sweden’s watercourses were altered. This decreased the amount of available spawning habitats for salmonids, and hence had a negative effect on the riverine brown trout (Salmo trutta) populations. Reconstruction of spawning grounds is today a common measure in restoration of altered streams in Sweden. However, very little evaluation of the effectiveness of these reconstructed spawning grounds exists. Hence, today we lack knowledge on how to further improve the construction of spawning habitats. In this study, conducted in boreal streams in northern Sweden, I have investigated the influence of several variables believed to have importance in spawning habitat selection for brown trout. I have investigated variables at two different scales, the patch scale (the microhabitat where the fish are spawning) and the bed scale (the macrohabitat that surrounds the spawning bed). My results suggest that the percentage of fines within the spawning substrate is an important predictor on probability of spawning at the patch scale. I also report moderate influence of water velocity, area and depth on probability of spawning at the patch scale. Distance to shore were found to have some influence on the selection of spawning bed by trout, while distance to cover for adult spawners, as well as distance to, and size of, nursery habitat were found to have low importance. To apply these findings for fish and wildlife managers I point out that raking and cleaning of gravel, and the placement of spawning beds further away from shore may be important measures to enhance the probability of spawning in reconstructed spawning habitats.